Biological Activity of Gold Compounds against Viruses and Parasitosis: A Systematic Review - Custódia Fonseca; Manuel Aureliano (MDPI AG, 2022)
In this contribution, we provide an overview of gold compound applications against viruses or parasites during recent years. The special properties of gold have been the subject of intense investigation in recent years, which has led to the development of its chemistry with the synthesis of new compounds and the study of its applicability in various areas such as catalysis, materials, nanotechnology and medicine. Herein, thirteen gold articles with applications in several viruses, such as hepatitis C virus (HCV), influenza A virus (H1N1), vesicular stomatitis virus (VSV), coronavirus (SARS-CoV and SARS-CoV-2), Dengue virus, and several parasites such as Plasmodium sp., Leishmania sp., Tripanossoma sp., Brugia sp., Schistosoma sp., Onchocerca sp., Acanthamoeba sp., and Trichomonas sp. are described. Gold compounds with anti-viral activity include gold nanoparticles with the ligands mercaptoundecanosulfonate, 1-octanethiol and aldoses and gold complexes with phosphine and carbene ligands. All of the gold compounds with anti-parasitic activity reported are gold complexes of the carbene type. Auranofin is a gold drug already used against rheumatoid arthritis, and it has also been tested against virus and parasites.